(Bacteriocin: Bio Preservatives from Lactic Acid Bacteria. Classifications, Screening and Purification Technique and its Application in Food Industry) - Yuliasri Ramadhani Meutia (Balai Besar Industri Agro, 2011)
Lactic acid bacteria (LAB) are known to have an antagonistic activity toward a variety of microorganisms Bacteriocin production from LAB is one of the properties responsible for the antibacterial activity against closely related species and possibly gram-positive food spoilers and pathogens bcteriocins produced by lactic acid bacteria are either small thermostable peptides or large thermolabile proteins .large numbers of bacteriocin producers have been found among different genera of the lactic acid bacteria .the diffusion method of bacteriocins on solid medium or antagonistic method as direct method and sport on the lawn and flip streak methods as indirect method can be used as screening of bacteriocin purification methods of bacteriocins can used ammonium sulphate precipitation ,ion exchange chromatography,hydrophobic interaction chromatography, and phase back high performance liquid chromatography. Bacteriocins are of interest for potential application in the food industry because of their antimicrobial activity and technologically favorable properties.